Rent-seeking resource and institutional challenges in Ghana’s nascent oil economy - Dartey-Baah, K.; Amponsah-Tawiah, K.; Aratuo, D. (Emerald Group Publishing Limited, 2014)
Purpose – The paper aims to assess the institutional readiness of Ghana prior to and after the production of her first oil. The paper also assesses the influence of politics in directing the appropriate use of the oil rents in facilitating the developmental needs of the country. Design/methodology/approach – The paper uses a literature review of the main theories regarding national politics and institutional policies in explaining the economic demise of a country due to a natural resource find. It also uses the natural resource find in Norway as a case study, drawing lessons from the effectiveness of Norway’s institutional policies in harnessing maximum benefits from their oil find and how developing nations such as Ghana can do same. Findings – The paper establishes that Ghana’s institutional architecture as regards the production of oil and gas is fraught with inadequacies on all fronts as regards regulations, regulators and the needed logistics. Additionally, the paper also highlights the role of Ghana’s political elite in perpetuating these institutional inadequacies. Originality/value – The paper highlights the insufficiencies in the institutional readiness for Ghana’s oil find and brings to the fore the influence of Ghana’s politics in contributing to these inadequacies.
Keywords: Ghana; Institutional architecture; Oil; Resource rents; Natural resource